Evaluating treatments and corresponding costs of prostate cancer patients treated within an inpatient or hospital-based outpatient setting. (February 2015) - Seal, Brian; Sullivan, Sean D; Ramsey, Scott; Asche, Carl V; Shermock, Kenneth M; Sarma, Syam; Zagadailov, Erin; Farrelly, Eileen; Eaddy, Michael
ABSTRACT : Aim: To describe treatments and cost of care for prostate cancer (PCa) in hospital-based outpatient and inpatient settings.Methods: Hospital encounters associated with PCa (ICD-9 codes 185, 233.4) and PCa-related treatment in a hospital claims database were included.Results: There were 211, 440 encounters for PCa between January 2006 and December 2010 (88, 151 inpatient and 123, 289 outpatient). Average cost per inpatient stay was US$12, 286 versus US$4364 per outpatient visit. Most common treatment during an inpatient stay and outpatient visit was surgery (57%) and radiation (76%), respectively. A total of 80% of outpatient visits and 69.9% inpatient stays were associated with a single treatment; remaining encounters were associated with ≥2 treatments.Conclusion: Costs are consistent with previous estimates; however, multimodal therapy is an emerging trend that may be related to greater costs in the future which may also be a challenge for hospital decision makers.